2019
DOI: 10.14745/ccdr.v45i09a02
|View full text |Cite
|
Sign up to set email alerts
|

Molecular surveillance of hepatitis C virus genotypes identifies the emergence of a genotype 4d lineage among men in Quebec, 2001–2017

Abstract: Background: Molecular phylogenetics are generally used to confirm hepatitis C virus (HCV) transmission events. In addition, the Laboratoire de santé publique du Québec (LSPQ) has been using molecular phylogenetics for surveillance of HCV genotyping since November 2001. Objectives: To describe the emergence of a specific lineage of HCV genotype 4d (G4d) and its characteristics using molecular phylogenetics as a surveillance tool for identifying HCV strain clustering. Methods: The LSPQ prospectively applied Sang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…A few previous works have been conducted about the recent emergence of HCV-4d. A strong connection between The Netherlands and Germany has already been observed as well as between Quebec and Europe [9,10]. Our work highlights close links between the French and The Netherlands MSM communities as emphasized by HCV transmission with several possible translocation events between these two countries within cluster A.…”
Section: Discussionsupporting
confidence: 66%
“…A few previous works have been conducted about the recent emergence of HCV-4d. A strong connection between The Netherlands and Germany has already been observed as well as between Quebec and Europe [9,10]. Our work highlights close links between the French and The Netherlands MSM communities as emphasized by HCV transmission with several possible translocation events between these two countries within cluster A.…”
Section: Discussionsupporting
confidence: 66%
“…Sequences were associated with a particular cluster if the nucleotides differed by less than 3% and the bootstrap support value was greater than 70% [ 21 ]. Monophyletic clusters and phylogenetic trees were derived from sequences that clustered using the maximum likelihood method.…”
Section: Methodsmentioning
confidence: 99%
“…In this report, up to 75% reported casual sexual partners sought online and 79% at sex venues, which would spread the HCV infection internationally, as demonstrated in a report from Canada. The latter showed that the GT4d isolates from HIV-infected and HIV-negative MSM had a closer relationship with isolates from several European countries, including isolates from the HEPAIG study 6 . In our study, a classical epidemiological link among our patients could not be achieved because the patient's samples were sent from several clinics in Mexico City, as well as was difficult to obtain reliable data from the patients after HCV4d diagnosis.…”
Section: Discussionmentioning
confidence: 67%
“…The hepatitis C virus (HCV), which was primarily identified as a pathogen transmitted by blood, is now a well-identified sexually transmitted infection affecting men who have sex with men (MSM), mainly with human immunodeficiency virus (HIV) infection 1 . Molecular phylogenetic studies have shown clusters of HCV transmission in HIV-infected patients MSM without any additional risk factors in several countries, such as France, 2 Germany, 3 Netherlands, 4 United States, 5 and showing transcontinental dissemination 6 . Moreover, HCV harboring NS5A resistance-associated substitutions (RASs) has been transmitted among HIV-infected and HIV-negative MSM, which would compromise the treatment of HCV infection with some direct-acting antiviral agents (DAAs) 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation